DEVELOPMENT OF INTERNATIONAL COOPERATION AND INVESTMENT PROCESSES IN THE TOURISM SECTOR IN UZBEKISTAN - Dr. Venkatarathnam , Nakka; Meliboyeva , Ma’mura (Scientific practical conference, 2025)
This thesis analyzes the development of the tourism sector in Uzbekistan, regional opportunities and international cooperation issues. The main focus is on the tourism potential of Samarkand, Khiva, Bukhara and Jizzakh regions. The article is based on statistical data for 2020–2025, resolutions and decrees of the President of the Republic of Uzbekistan on the development of tourism, as well as reports of the World Tourism Organization (UNWTO). As a result of the research, conclusions and proposals were developed on the development of the country's tourism infrastructure, attracting investments and forming new types of tourism.